The Use of Plant Essential Oils as Feed Additives for Ruminants - Muhamad N Rofiq (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2016)
Public awareness of health risk and environmental problem caused by unappropriate use of antibiotics and hormones resulted in prohibition of antibiotics in feed since 2003 in European Union. The regulation stated that ruminant feed additives should not have an adverse effect on animal health, human health and environment. Plant essential oils are recommended for animal feed additive because of their antimicrobial effects. The major bioactive compounds of essential oils as rumen manipulator have not been yet evaluated on in vitro and in vivo studies. Some plants essential oils showed their function to increase dry matter digestibility, rumen VFA products, N-NH3 and reduce rumen methane production in the in vitro study. The studies still have not enough yet to prove the use of essential oils as ruminant feed additive to increase nutrient digestibility and mitigate rumen methane production. Combination of some plant essential oils or some of their main active components may be more advantageous because of their sinergistic effects.